2015
DOI: 10.2355/isijinternational.55.805
|View full text |Cite
|
Sign up to set email alerts
|

Instability and Periodicity of Asymmetrical Flow in a Funnel Thin Slab Continuous Casting Mold

Abstract: Characteristics of the transient turbulent flow in a funnel thin slab continuous casting mold are studied using a large eddy simulation (LES) computational approach. Validations were done through comparison with previous experimental data of the mean velocities and the instantaneous velocities, and good qualitative and quantitative agreements are obtained. The turbulence flow inside the mold consists of various scales vortices; many pronounced large scale vortex structures were clear found inside the mold, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In literature, various SEN models have been proposed to satisfy the demand for high-quality steel. For example, based on thin slab technology, the angle of the SEN exit ports could also be directed upward to avoid fluctuations in the liquidfree surface [7,19]. Additionally, a larger number of exit ports have been observed to improve the steel distribution to the mold [7].…”
Section: Introductionmentioning
confidence: 99%
“…In literature, various SEN models have been proposed to satisfy the demand for high-quality steel. For example, based on thin slab technology, the angle of the SEN exit ports could also be directed upward to avoid fluctuations in the liquidfree surface [7,19]. Additionally, a larger number of exit ports have been observed to improve the steel distribution to the mold [7].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have shown that inclusion distribution is largely affected by the flow field. Among these studies, the periodical biased flow is identified and characterized by water model, and is used to interpret the asymmetry distribution of inclusions in slab. However, the reason for the special distribution found in Figure , is still unknown.…”
Section: Numerical Results For Inclusion Distributionmentioning
confidence: 99%
“…The thin slab casting process is an example of the technological improvements in steel production; nevertheless, due to its high casting velocities and the small slab thickness, the liquid steel inside produces complex turbulent phenomena adversely affecting the final product quality. On this line, many researchers have focused their efforts on studying these turbulent phenomena, searching for a deeper understanding of how to control or eradicate them [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Some of the most commonly observed phenomena are asymmetries and oscillations of the flow patterns inside the mold, identified through mathematical simulations [2,4,5,7,10,11,[14][15][16][17][18][19] or by physical modeling [6,[9][10][11][12][13][15][16][17], formation of strong recirculation at each SEN side [7][8][9][10][11]…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most commonly observed phenomena are asymmetries and oscillations of the flow patterns inside the mold, identified through mathematical simulations [2,4,5,7,10,11,[14][15][16][17][18][19] or by physical modeling [6,[9][10][11][12][13][15][16][17], formation of strong recirculation at each SEN side [7][8][9][10][11][12][13][14][15][16][17][18][19], meniscus fluctuations [8][9][10][11][12][13][14][15][16][17]19], meniscus vortex formation [10][11][12][17][18]…”
Section: Introductionmentioning
confidence: 99%